Off-the-Shelf OFDM-ISAC System with Clustering Algorithm for Multipath Environments - Lee, Ha Eun; Lee, Young Seok; Jung, Bang Chul (IEEE Wireless Communications and Networking Conference, WCNC, 2025)
Recently, integrated sensing and communication (ISAC) techniques have gained significant attention due to their ability to simultaneously perform sensing, localization, and communication using shared wireless resources and signal waveforms, thereby enhancing spectral and cost efficiency. Orthogonal frequency division multiplexing (OFDM) is also expected to remain a key technology in next-generation mobile communication systems due to its robustness against multipath fading and its strong support for high data rates. Building on these points, we propose a novel orthogonal sequence (OS)- based OFDM-ISAC technique fully compatible with conventional OFDM-based communication systems. This technique intelligently exploits the autocorrelation properties of OSs and the spectral efficiency of index modulation while incorporating a clustering algorithm to address challenges in multipath environments. Extensive computer simulations verify that the proposed OFDM-ISAC system delivers reliable communication and localization performance in realistic multipath environments. even in the absence of a line-of-sight (LOS) link.
Keywords: 6g; Communications systems; Integrated sensing; Integrated sensing and communication; Multipath environments; Orthogonal frequency division multiplexing; Orthogonal frequency-division multiplexing; Orthogonal sequences; Sensing systems; Wireless localization; 6G; Integrated sensing and communication (ISAC); Orthogonal frequency division multiplexing (OFDM); Orthogonal sequence; Wireless localization